Comparison of seven chemical pretreatments of corn straw for improving methane yield by anaerobic digestion. - Zilin Song; GaiheYang; Xiaofeng Liu; Zhiying Yan; Yuexiang Yuan; Yinzhang Liao (PLoS ONE, 2014)
Agriculture straw is considered a renewable resource that has the potential to contribute greatly to bioenergy supplies. Chemical pretreatment prior to anaerobic digestion can increase the anaerobic digestibility of agriculture straw. The present study investigated the effects of seven chemical pretreatments on the composition and methane yield of corn straw to assess their effectiveness of digestibility. Four acid reagents (H2SO4, HCl, H2O2, and CH3COOH) at concentrations of 1%, 2%, 3%, and 4% (w/w) and three alkaline reagents (NaOH, Ca(OH)2, and NH3·H2O) at concentrations of 4%, 6%, 8%, and 10% (w/w) were used for the pretreatments. All pretreatments were effective in the biodegradation of the lignocellulosic straw structure. The straw, pretreated with 3% H2O2 and 8% Ca(OH)2, acquired the highest methane yield of 216.7 and 206.6 mL CH4 g VS(-1) in the acid and alkaline pretreatments, which are 115.4% and 105.3% greater than the untreated straw. H2O2 and Ca(OH)2 can be considered as the most favorable pretreatment methods for improving the methane yield of straw because of their effectiveness and low cost.